KEBERADAAN KEBIASAAN NGINANG PADA MASYARAKAT MELAYU DI KECAMATAN SEBERANG ULU I KOTA PALEMBANG - Suryo Arief Wibowo; Endang Rochmiatun; Amilda Amilda (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 2021)
The progress of the times and the ease with which foreign cultures enter the life of the current generation have made a lot of local wisdom begin to experience degradation to the point of extinction. As is the case, the younger generation of Palembang Malay descent, at this time has left a tradition that has been passed down from generation to generation, namely the nginang tradition. Nginang is a habit that has become a hereditary tradition carried out by the Malay community in Sumatra and Palembang. This study aims to reveal the phenomenon of the habit of nginang which is still carried out by some Malay people in Palembang. This research uses descriptive-qualitative research using ethnographic method which is an approach to anthropology disciplines. Sources of data used are primary data sources and secondary sources. Primary sources that come from people who nginang and cultural. Secondary sources come from research reports, books, archives, and so on. The data collection technique used direct observation to the location, namely in Seberang Ulu I District, Palembang City. As for using participant interviews, namely key informants as the main data and using relevant literature studies to support this research as well as collecting audio-visual materials in the form of photos, images and sounds that come from the betel nut and cultural observers. Data analysis will be directly in conjunction with other parts of the development of this research, namely data collection and writing of findings. In this study, it was found that this habit is still used by some of the Palembang Malay community who are female, this is due to the emergence of public stigma against men against the habit of nginang which is only identified with cigarettes. The habit of nutmeg is starting to disappear due to family factors, the progress of the times, the environment and community institutions.